Numerical modelling and experimental analysis of acoustic emission; Journal of Physics: Conference Series; Vol. 1015 : Information Technologies in Business and Industry (ITBI2018) - Gerasimov S. I. Sergey Ivanovich (Mathematical simulation and data processing, 2018)
Title screen